(3HjGf eTcd CMGOjK QShd Gddg Udi Gddg Ydjg hSdes - (3GdWMGhj , CHh LYaQ,J (B321 (3g` s ((3CMeO Hf eMeO Hf efUhQ Hf gGTe GdTgjQ HGdahi s)
(3ChdgG (B:s
(3jHOC HHGH HjGf eTcd eG Qhi Yf QShd Gddg Udi Gddg Ydjg hSde ajeG cGf CSQg gd ef cGf CSQg Edjg Gf jHOjg ai MjGJg Ch HYO haGJg s
(3BNQgG (B:s
(3jfJgi HHGH HjGf eTcd eG Qhi Yf QShd Gddg Udi Gddg Ydjg hSde ajeG cGf efg ai HQjQI deG SCd CgdgG YGFTI s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B206 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B107s
Keywords: (3GdMOjK h GdeUWdMs